1988
DOI: 10.1007/bf01798350
|View full text |Cite
|
Sign up to set email alerts
|

Sleeping on a wedge diminishes exposure of the esophagus to refluxed acid

Abstract: In a randomized crossover study, we compared the effect on gastroesophageal reflux of three sleeping positions: elevation of the head of the bed on standard eight-inch bed blocks; elevation by a foam wedge; or a flat position. Fifteen subjects with moderate to severe reflux symptoms were studied in each position on consecutive nights using continuous intraesophageal pH monitoring. We found no difference in reflux frequency among the positions. The wedge caused a statistically significant decrease in the time t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
3

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(62 citation statements)
references
References 9 publications
0
59
0
3
Order By: Relevance
“…Randomized trials have shown that this practice can decrease esophageal acid exposure and lead to shorter reflux periods and a rapid esophageal clearance [Hamilton et al 1988]. Elevating the head of the bed is important for people with nocturnal or laryngeal symptoms.…”
Section: Sleep Positionmentioning
confidence: 99%
“…Randomized trials have shown that this practice can decrease esophageal acid exposure and lead to shorter reflux periods and a rapid esophageal clearance [Hamilton et al 1988]. Elevating the head of the bed is important for people with nocturnal or laryngeal symptoms.…”
Section: Sleep Positionmentioning
confidence: 99%
“…Stanciu and Bennett 80 compared the effect of different body positions (sitting, lying, and elevated HOB) in 63 patients with GERD symptoms using pH monitoring and showed that compared with patients who slept flat, patients who slept with an elevated HOB (using 28-cm blocks) had significantly fewer reflux episodes, shorter reflux episodes, faster acid clearing, and fewer reflux symptoms. Hamilton et al 94 conducted a randomized clinical trial comparing sleeping on a wedge, sleep with HOB elevation, and sleeping in the horizontal position and found that sleeping on a wedge was associated with significantly less esophageal acid exposure compared with sleeping in the horizontal position. Sleeping with HOB elevation also showed improved acid exposure, but this difference was not statistically significant.…”
Section: Recumbent Position and Hob Elevationmentioning
confidence: 99%
“…The wedge caused a statistically significant decrease in the time that the distal oesophageal pH was <4 as compared to the flat position. Elevation on blocks caused an improvement in parameters, but this was not statistically significant [5] .…”
Section: Introductionmentioning
confidence: 70%